Comparison of Inter-Canine and Inter-Molar Width as an Aid in Gender Determination: A Preliminary Study - Daniel, M Jonathan; Khatri, Mihir; Srinivasan, SV; Jimsha, VK; Marak , Fremingston (Journal of Indian Academy of Forensic Medicine, 2014)
The dentition use in gender determination has been explored and advocated owing to its strength  and resistance to various insults. Our aim was to determine and evaluate the usefulness of inter-molar  arch width in gender determination. Our objective was to compare these distances in determination of  gender and to validate its use as a forensic tool. Fifty subjects were selected and impressions were made  for both the arches with alginate. Study models were prepared and used for analysis.  Inter-canine and inter-molar width in maxillary arch for male and female were 35.22 ± 1.54 and  33.49 ± 1.49; and 48.74 ± 1.89 and 45.44 ± 1.92 respectively. Inter-canine and inter-molar width in  mandibular arch for male and female were 25.58 ± 1.37 and 25.29 ± 1.50; and 42.45 ± 2.00 and 39.53 ±  1.87 respectively. Thus, these measurements were significantly higher in males. On using the Receiver  Operating Characteristic (ROC) curve to deduce values with high specificity maxillary inter-molar arch  width gave high specificity of 92% to detect gender correctly, with best sensitivity i.e. 64%. Therefore, we  conclude that inter-molar arch width is useful in determining the gender of dental remains accurately, of  individuals with missing canine teeth.
Keywords: Maxillary arch; Mandibular arch; Inter-canine arch width; Inter-molar arch width; Gender determination